Gut histology of Malaysian river catfish, Mystus nemurus (C&V) larvae - El Hag, Ghada Ahmed; Kamarudin, Mohd Salleh; Saad, Che Roos; Daud, Siti Khalijah (Marsland Press, 2012)
For the successful weaning of M. nemurus larvae, the development of gut histology was observed. The eggs hatched two days after firtelization (2 daf) and most of the larvae hatched within 2-4 daf. The commencement of external feeding start on the 4 days post-hatch (dph). Fish larvae are charactrized by digestive system and diets that differ from adults. Larvae undergo a pattern of trophic ontogeny, changing with inceasung size, and these changes result in differences in digestive requierments. The histological development of the gut of M. nemurus larvae were investigated from hatching untile 21dph using a compound microscopy. During the yolk sac period, the gut is a simple, straight, undifferntiated tube thrghout its length.by 4-5 dph the gut differentiated to the oesophgus, stomach, and intestine. At first feeding, the larval gut is functional, but is structurally and functionally less complex than that of adults.By the 13 dph the larvae attained four tissue layers arrangement.